Legal collisions for establishing tax benefits on land tax (the example of the Free port of Vladivostok) - Svetlana M. Mironova (Правоприменение, 2020)
The subject. The analysis of the establishment of land tax benefits for residents of the Free Port of Vladivostok by municipalities is carried out.The purpose of the article is to determine the feasibility of establishing land tax benefits for residents of the Free Port of Vladivostok (FPV) by the municipalities themselves or to confirm the need for federal regulation of the establishment of such benefits by the Tax Code of the Russian Federation.The methodology of the study includes the analysis of municipal legal acts on the establishment of land taxes in municipalities that are parts of the FPV.The main results and scope of their application. Due to the limitation of powers of municipalities located in territories with special legal status, one of the powers that such municipalities exercise is the establishment of local taxes and fees, as well as local tax benefits for residents of such territories. In most cases, such benefits provided at the federal level, so municipalities only “exercise the will” of the federal legislator by imposing a local tax on their territory. Due to the absence of federal regulation, tax benefits on local taxes will be established at the discretion of local authorities, which may lead to competition and unequal economic conditions for residents. So, for residents of the Free Port of Vladivostok (which includes 22 municipalities located in five constituent entities of the Russian Federation) in the absence of federal regulation, the municipal entities themselves will establish land tax benefits, which in practice leads to differentiation in the payment of land tax in the territory of the Free Port of Vladivostok. All municipalities that are parts of the FPV are divided into three groups: 1) a land tax exemption has been established in the municipalities of the first group; 2) the municipalities of the second group has not established a land tax benefit; 3) the municipalities of the third group have a zero land tax rate. It is necessary to establish a common list of benefits on the territory of the FPV by the Tax Code of the Russian Federation with the possibility of expanding such benefits at the regional and municipal levels, taking into account local characteristics.Conclusions. Municipalities establish the land tax benefits in different ways, and such situation leads to an unequal economic situation for residents of FPV. In order to remove competition between municipalities and due to the significance of the goals that the state sets for itself, creating territories with special economic status, it seems necessary to establish a typical list of benefits on such territories at the federal level by the Tax Code of the Russian Federation with the possibility of expanding such benefits at regional and municipal level according to local circumstances.